2011
DOI: 10.2522/ptj.20100292
|View full text |Cite
|
Sign up to set email alerts
|

An Obese Body Mass Increases the Adverse Effects of HIV/AIDS on Balance and Gait

Abstract: The present findings have an obvious and unfortunate implication: as more patients who are HIV-1 seropositive join the seronegative community in becoming obese, the effects of obesity and their disease may summate and their risk for balance and gait problems may increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 34 publications
0
52
1
Order By: Relevance
“…However, we did not find differences in objective testing of vestibular function between the HIV-infected and HIV-uninfected men and women in this same cohort [18], and found no association between falls and symptoms of vertigo in the current analysis. Prior studies have shown impairments in objective measures of imbalance in approximately 10% of middle-aged HIV-infected persons on effective ART [11,41], with HIVinfected persons demonstrating poorer performance on objective laboratory or clinically based imbalance measures compared with HIV-uninfected controls [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find differences in objective testing of vestibular function between the HIV-infected and HIV-uninfected men and women in this same cohort [18], and found no association between falls and symptoms of vertigo in the current analysis. Prior studies have shown impairments in objective measures of imbalance in approximately 10% of middle-aged HIV-infected persons on effective ART [11,41], with HIVinfected persons demonstrating poorer performance on objective laboratory or clinically based imbalance measures compared with HIV-uninfected controls [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and the metabolic syndrome are established risk factors for the development of physical function impairment or frailty among middle-aged or older HIV-infected adults[9093]. Obesity has also been associated with fall risk in HIV-infected women[94].…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%
“…Obesity and the metabolic syndrome are well-established risk factors for the development of physical function impairment or frailty among geriatric HIV-uninfected populations [18] and middle-aged or older HIV-infected adults [19-21]. Similarly, obesity is a known risk factor for diabetes mellitus and cardiovascular disease (CVD), and increased CVD risk has been described among obese and lipohypertrophic, HIV-infected adults [22].…”
Section: Discussionmentioning
confidence: 99%